Physiological characteristics of the preferred transition speed in racewalkers - Ziv, G.; Rotstein, A. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The preferred transition speed (PTS) at which humans change their gait from walking to running was found to be lower than their energetically optimal transition speed (EOTS). This phenomenon has not been examined in racewalkers. The purpose of this study was to evaluate the PTS and the EOTS in racewalkers compared with controls.